SOIL TEST BASED NUTRIENT MANAGEMENT FOR RABI SUNFLOWER (Helianthus annuus L.) - K. PRABHAKAR, P. MUNIRATHNAM, S. BALAJI NAYAK, K. VENKATARAMANAMMA, T. RAGHAVENDRA, P. PULLI BAI; B. GOPAL REDDY (The Journal of Research ANGRAU, 2017)
A field experiment was conducted for two rabi seasons (2014-15 and 2015-16) at Regional Agricultural Research Station, Nandyala, Andhra Pradesh to study the influence of different levels of soil test based nutrient management on yield attributes, seed yield, plant nutrient uptake and available soil nutrient status of sunflower. The results revealed that the maximum plant height (cm), capitulum diameter (cm), capitulum weight(g), single plant yield (g), stalk yield kg ha-1 and seed yield (2683 kg ha-1) were obtained with STCR approach + VC @ 2 t ha-1. While the minimum values of yield attributes and seed yield (1015 kg ha-1) and yield attributes were recorded with farmers practice. The study indicated that nutrient management based on soil tested data lead to positive nutrient balance.